FRI0595 Responsiveness and Test-Retest Reliability of New Disease Assessment Instruments in Systemic Lupus Erythematosus in Relation To SLEDAI-2K. (15th July 2016) - Chatham, W.W.; Collins, C.E.; Gaylis, N.; Busch, H.; Hautamaki, E.; Narayanan, S.
Abstract : Background: Several new simplified Disease Assessment Instruments/Indices (DAIs) in Systemic Lupus Erythematosus (SLE) are in different stages of development to aid easy use in daily clinical practice, including SLE Activity Tracking Evaluation Tool (LAST; 14 items; includes medications, Physician Global Assessment (PhGA) 0–10 scale, Patient Global Assessment (0–10 scale), C3/C4/anti-dsDNA measures), Clinical LAST (C-LAST; 11 items; similar to LAST, without lab measures), Total Lupus Activity Score (TLAS; 30 items on lupus symptoms, with 15 each of physician clinical & patient self-assessments), and Simple Disease Assessment for People with Lupus Erythematosus (SIMPLE; 17 items; includes patient self-assessment of lupus symptoms, Lupus Impact Tracker, steroid medication, C3/C4/proteinuria). Objectives: To assess responsiveness and test-retest reliability of the DAIs between baseline (BL) and 3mo assessments. Methods: This is a prospective real-world observational cohort study of SLE patients receiving standard care in two private and two academic sites in the US. Respective portions of DAIs (incl. SLEDAI-2K & PhGA (0–3 scale) (in all sites) & BILAG-2004 (in academic sites)) are completed by physicians and patients at four time points: BL/3mo/6mo/12mo. Responsiveness was assessed by analyzing within-person change in scale scores and effect size (mean change divided by standard deviation of BL score) between BL and 3mo in relation to change in clinical status, as measured by SLEDAI-2K scores, categorized as "improved", "no change", or "worsened", and test-retest reliability was assessed by Spearman correlation coefficient (rs ) comparing BL and 3mo scores among those with "no change" in SLEDAI-2K scores. Correlations (rs ) between BILAG-2004 and other DAI scores were assessed. Results: In total, 201 patients (mean age: 45 yrs; female: 91%; Black/African American: 56%; Hispanic: 10%) were enrolled in the study; 149 patients with BL baseline and 3mo data were evaluated. Within-person change/effect size among the Improved group (n=54): LAST = -6.4/-0.537, C-LAST = -5.6/-0.536), TLAS = -1.7/-0.234, SIMPLE = -4.1/-0.359, PhGA (0–10) = -1.3/-0.655, PhGA (0–3) = -0.7/-0.915; No change (n=55): LAST = -0.7/-0.055, C-LAST: -0.5 /-0.049, TLAS: 1.7/.159, SIMPLE: -1.3/-0.114, PhGA (0–10) = -0.2/-0.080, PhGA (0–3): -0.02/-0.025; Worsened (n=40): LAST = 4.1/0.323, C-LAST = 2.9/0.265, TLAS = 4.8/0.449, SIMPLE = 1.9/0.170, PhGA (0–10) = 1.0/0.495, PhGA (0–3) = 0.4/0.480. Test-retest reliability was (rs ; all p<0.0001): LAST = 0.713, CLAST = 0.684, TLAST = 0.778, SIMPLE = 0.757, PhGA (0–10) = 0.639, PhGA (0–3) = 0.503). At 3mo, BILAG-2004 correlated with DAIs as (r/n): LAST = 0.465/59 (p=0.0002), C-LAST = 0.391/59 (p=0.0022), TLAS = 0.280/56 (p=0.0366), SIMPLE = 0.627/56 (p<0.0001), PhGA (0–10) = 0.553/59 (p<0.0001), PhGA (0–3) = 0.507/71 (p<0.0001). Conclusions: Test-retest reliability showed moderate-to-strong correlations between baseline and 3mo assessments. For the "improved" and "worsened" groups (per SLEDAI-2K change), effect sizes indicated a small to medium effect, whereas the "no change" group had effect sizes indicative of no change; mean within-person change scores were directionally responsive to clinical change. Most DAIs had moderate correlation to BILAG-2004. Disclosure of Interest: W. W. Chatham Grant/research support from: GlaxoSmithKline, C. Collins Grant/research support from: GlaxoSmithKline, N. Gaylis Grant/research support from: GlaxoSmithKline, H. Busch Grant/research support from: GlaxoSmithKline, E. Hautamaki Employee of: Ipsos Healthcare, which consults for GlaxoSmithKline and other pharmaceutical companies, S. Narayanan Employee of: Ipsos Healthcare, which consults for GlaxoSmithKline and other pharmaceutical companies